Hydrothermally prepared ultra-stable multilayer nanoflake NiO-based electrochromic films. (10th February 2023) - Xu, Kejun; Wang, Liuying; Xiong, Shanxin; Ge, Chaoqun; Wang, Long; Wang, Bin; Wang, Weichao; Chen, Mengzhou; Liu, Gu
Abstract: Electrochromic materials cycle between colored and bleached states under various applied voltage and have applications in smart windows and displays. The formation of a micro–nano structure in electrochromic thin films using hydrothermal methods can improve their properties. However, the conventional constant-temperature hydrothermal method yields films that easily peel from the conductive substrate during electrochromic cycling, resulting in performance losses. Therefore, we investigated the effect of a gradient-temperature hydrothermal protocol on the electrochromic performance of NiO thin films. First, a layer of small, strongly adhered crystal grains was seeded on an indium tin oxide substrate. Thereafter, NiO nanoflake layers were grown by adjusting the reaction temperature. The prepared film could be operated for 14, 000 electrochromic cycles, four-times more than those of the conventionally prepared films, without significant performance loss. Therefore, our proposed method enhances the cyclic stability of micro–nanostructured NiO thin films significantly and will aid the development of high-performance electrochromic thin films having broad applications.